Therapeutic implications of the warburg effect assessing the survival of MRC5 and a549 cell lines upon exposure to honey and d glucose - biomed 2013 - Farah, Ibrahim O; Lewis, Veshell L; Ayensu, Wellington K; Cameron, Joseph A (Biomedical sciences instrumentation, 2013)
Lung cancer is a one of the most prevalent and deadly cancers in United States. Experimental evidence support that cancer cells do exhibit higher glycolytic rates than normal cells. To exploit this unique cancer-dependent ATP generation phenomenon, we hypothesize that exposure of cancer cells to organic inhibitors of glycolysis would negatively impact their survival and alter their growth and viability resulting from the vast decrease in their essential glycolytic ATP production; no negative consequences will be seen on normal lung cells. The human lung fibroblast cell line MRC-5 and the human lung alveolar epithelial cancer cell line A549 were used in this study as models for normal lung and lung cancer respectively. Using standard methods, both cell lines were maintained and exposed to honey and D-glucose reagents at concentration levels ranging from 31.3-2,000 µg/ml in 96 well plates in quadruplets and experiments repeated at least three times using MTT (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide), and cell counting (T4 Cellometer; automated cell counting system) assays as well as phase-contrast photo-imaging. Our results indicate that exposure of both cell lines to these organics lead to concentration dependent cell destruction/cell survival depending on the cell line exposed. Honey and D-glucose showed statistically significant (p<0.05) differential negative effects on the A549 line in comparison to its unexposed control as well as to their effects on the MRC-5 cell line. These findings show a promising role for honey and D-glucose as biotherapeutic metabolites of interest for selective management of cancerous cells.